Parent-Based Child Sexual Abuse Prevention Programs: A Systematic Literature Review - Agninda Rahmi Putri; Tutut Chusniyah (Universitas Al-Hikmah Indonesia, 2025)
Cases of child sexual abuse (CSA) in Indonesia continue to rise annually, representing a serious social and public health concern. Parents play a crucial role in preventing CSA, as they can directly teach children about bodily autonomy and safety. However, many parents lack awareness, hold misconceptions, and feel uncomfortable discussing sexual matters with their children. Despite their importance, interventions targeting parents remain limited, with most programs focusing primarily on children. This study aims to identify factors influencing parental awareness of CSA prevention and to examine parent-focused interventions through a systematic literature review (SLR). Data were collected from Google Scholar, Springer, Taylor & Francis, Sage, and ScienceDirect using Publish or Perish (PoP) software, applying inclusion criteria and the PRISMA framework. Thirteen relevant articles published within the past ten years were analyzed. Findings indicate that economic status, education level, limited knowledge, and negative attitudes significantly affect parents’ ability to educate their children about CSA prevention. In Indonesia, parent-focused interventions primarily include the “Underwear Rules” program and psychoeducational sessions using lectures, audiovisual media, worksheets, and roleplay. Internationally, interventions are more diverse, including structured training and game-based approaches, which enhance parental confidence, knowledge, and communication skills. These findings highlight the importance of culturally sensitive programs that actively involve parents as central agents in preventing CSA.